2014
DOI: 10.1074/jbc.m114.576652
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Actions of the AAA-ATPase Valosin-containing Protein (VCP)/p97 and the Proteasome 19 S Regulatory Particle in Sterol-accelerated, Endoplasmic Reticulum (ER)-associated Degradation of 3-Hydroxy-3-methylglutaryl-coenzyme A Reductase

Abstract: Background: Mechanisms for sterol-and geranylgeraniol-induced dislocation of reductase from ER membranes into cytosol for degradation are unclear. Results: VCP/p97 mediates extraction of reductase across ER membranes, whereas the proteasome 19 S regulatory particle (RP) dislodges extracted reductase into cytosol. Conclusion: VCP/p97 and proteasome 19 S RP mediate sequential steps in reductase degradation. Significance: These results define a new step in the reductase degradative pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 48 publications
2
42
0
1
Order By: Relevance
“…1. membranes of the ER (panels 5 and 14, respectively). The remaining SCD-associated mutants of UBIAD1 were similarly defective in transport to the Golgi and localized to the ER (panels 3, 4, 6-13, and [15][16][17][18][19][20][21][22]. However, it should be noted that four SCD-associated UBIAD1 mutants, D112G (panel 6), D118G (panel 7), R119G (panel 8), and N232S (panel 18), exhibited partial Golgi localization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1. membranes of the ER (panels 5 and 14, respectively). The remaining SCD-associated mutants of UBIAD1 were similarly defective in transport to the Golgi and localized to the ER (panels 3, 4, 6-13, and [15][16][17][18][19][20][21][22]. However, it should be noted that four SCD-associated UBIAD1 mutants, D112G (panel 6), D118G (panel 7), R119G (panel 8), and N232S (panel 18), exhibited partial Golgi localization.…”
Section: Resultsmentioning
confidence: 99%
“…Maximal degradation requires the addition to cells of geranylgeraniol (GGOH), the alcohol derivative of GGpp (16). We postulate that GGOH becomes converted to GGpp, which augments reductase ERAD by enhancing its membrane extraction (21). Recently, we found that sterols also cause reductase to bind to UBIAD1 (12).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Insig binding is mediated entirely by the membrane domain of HMGCR, which contains eight transmembrane helices and precedes a cytosolic catalytic domain (7,8). Insig-associated ubiquitin ligases facilitate ubiquitination of cytosolically exposed lysine residues in the membrane domain of HMGCR (9 -11), marking the enzyme for extraction across ER membranes and dislocation into the cytosol for proteasomal degradation (12,13).…”
Section: Reductase (Hmgcr) Is a Polytopic Protein Of Endoplasmic Retimentioning
confidence: 99%
“…TRC8, MARCH6, and gp78 were identified as 3 key membraneanchored E3 ubiquitin-protein ligases involved in 25HC-stimulated HMGCR degradation (Song et al 2005;Jo et al 2011;Zelcer et al 2014). Subsequently, HMGCR is extracted from the ER membrane into the cytosol in a valosincontaining protein (VCP/p97)-dependent manner, enabling HMGCR degradation by the 26S proteasome (Elsabrouty et al 2013;Morris et al 2014). Through this mechanism, 25HC inhibits the rate-limiting step of cholesterol biosynthesis.…”
Section: Hc: Oxysterol Regulator Of Sterol Homeostasismentioning
confidence: 99%